Cortical Cross-Frequency Coupling Is Affected by in utero Exposure to Antidepressant Medication - Tokariev, Anton; Oberlander, Victoria C.; Videman, Mari; Vanhatalo, Sampsa (Frontiers in Neuroscience, 2022)
Up to five percent of human infants are exposed to maternal antidepressant medication by serotonin reuptake inhibitors (SRI) during pregnancy, yet the SRI effects on infant’s early neurodevelopment are incompletely understood. Here, we studied how maternal SRI medication affects cortical frequency-specific and cross-frequency interactions as measured by phase-phase correlations and phase-amplitude coupling, respectively. We examined the cortical activity in infants after fetal exposure to SRIs relative to a control group of infants without medical history of any kind. Our findings show that the sleep-related dynamics of phase-phase correlation networks are selectively affected by in utero SRI exposure, however those alterations don’t correlate to later neurocognitive development as tested by neuropsychological evaluation at two years of age. In turn, phase-amplitude coupling was found to be suppressed in SRI infants across multiple distributed cortical regions and these effects were linked to their neurocognitive outcomes. Our results are compatible with the overall notion that in utero drug exposures may cause subtle, yet measurable changes in the brain structure and function. Our present findings are based on the measures of local and inter-areal neuronal interactions in the cortex which can be readily used across species, as well as between different scales of inspection: from the whole animals to in vitro preparations. Therefore, this work opens a framework to explore the cellular and molecular mechanisms underlying neurodevelopmental SRI effects at all translational levels.